Brief counselling after home‐based HIV counselling and testing strongly increases linkage to care: a cluster‐randomized trial in Uganda. (20th October 2017) - Ruzagira, Eugene; Grosskurth, Heiner; Kamali, Anatoli; Baisley, Kathy
Abstract: Introduction: The aim of this study was to determine whether counselling provided subsequent to HIV testing and referral for care increases linkage to care among HIV‐positive persons identified through home‐based HIV counselling and testing (HBHCT) in Masaka, Uganda. Methods: The study was an open‐label cluster‐randomized trial. 28 rural communities were randomly allocated (1:1) to intervention (HBHCT, referral and counselling at one and two months) or control (HBHCT and referral only). HIV‐positive care‐naïve adults (≥18 years) were enrolled. To conceal participants' HIV status, one HIV‐negative person was recruited for every three HIV‐positive participants. Primary outcomes were linkage to care (clinic‐verified registration for care) status at six months, and time to linkage. Primary analyses were intention‐to‐treat using random effects logistic regression or Cox regression with shared frailty, as appropriate. Results: Three hundred and two(intervention, n  = 149; control, n  = 153) HIV‐positive participants were enrolled. Except for travel time to the nearest HIV clinic, baseline participant characteristics were generally balanced between trial arms. Retention was similar across trial arms (92% overall). One hundred and twenty‐seven (42.1%) participants linked to care: 76 (51.0%) in the intervention arm versus 51 (33.3%) in the control arm [odds ratio = 2.18, 95% confidence interval (CI) = 1.26–3.78; p  = 0.008)]. There was evidence of interaction between trial arm and follow‐up time ( p  = 0.009). The probability of linkage to care, did not differ between arms in the first two months of follow‐up, but was subsequently higher in the intervention arm versus the control arm [hazard ratio = 4.87, 95% CI = 1.79–13.27, p  = 0.002]. Conclusions: Counselling substantially increases linkage to care among HIV‐positive adults identified through HBHCT and may enhance efforts to increase antiretroviral therapy coverage in sub‐Saharan Africa.